Witnesses to the miracle - Blanco, Katiuska (Abril Publishing House, 2004)
An easterly bridge joins Bolivarian Venezuela to Cuba and leads the way to a world of light. Sight is like a child's kite, a comet: it sets a dream on a skyward course and travels far, in an explosion of lights and hues. This book recounts the histories of those who recovered hope, a firm step, joy and life itself.They are testimonies from the one end of the country to the other, given in the intense heat of August, 2004. Witness to the miracle.